Winding type battery and application thereof

By adding layer interval between the corner area of ​​the lithium -ion battery and using the compressed polymer coating, the problem of lithium -ion batteries analyzed the lithium during the large magnification of the existing lithium ion battery, and improved the preservation capacity of the electrolyte. The cycle performance of the battery.

CN119381584APending Publication Date: 2025-01-28HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411461846.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The separators of existing lithium-ion batteries have poor liquid retention properties for the electrolyte, which leads to prone to lithium extraction during the high-speed charging process, especially in the corner areas of the battery cell.

Method used

A rolling battery is designed, which adds a layer spacing between the positive and negative electrode in the corner area, and a compressed polymer coating is set on the septum. The compressed ratio is between 40 % and 70 % In order to improve the ability of electrolyte.

Benefits of technology

By increasing the laminar spacing of the corner area and optimizing the polymer coating of the diaphragm, it significantly improves the infiltration rate and amount of the electrolyte, reducing the risk of lithium analysis in the corner area of ​​the battery cell, and improving the cycle performance and energy density of the battery Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092072060000141
    Figure BDA0005092072060000141
  • Figure BDA0005092072060000152
    Figure BDA0005092072060000152
  • Figure BDA0005092072060000161
    Figure BDA0005092072060000161
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to a winding type battery and application thereof. The wound battery comprises a positive pole piece, a diaphragm and a negative pole piece which are wound in a laminated manner, and comprises a straight area and corner areas connected to two ends of the straight area, wherein in the corner region, the maximum distance between the adjacent positive pole piece and negative pole piece is A [mu] m; in the straight area, the maximum distance between the adjacent positive pole piece and negative pole piece is B [mu] m, and A-B is greater than or equal to 3 and less than or equal to 10; in addition, the diaphragm comprises a matrix and a polymer coating arranged on the surface of at least one side of the matrix, the compression ratio of the polymer coating is C, and C is larger than or equal to 40% and smaller than or equal to 70%; the polymer coating comprises polymer particles with the particle size Dv50 of 2-20 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a wound battery and applications thereof. Background Art

[0002] In recent years, the rapid development of portable electronic products and electric vehicles has put forward higher requirements for the performance of lithium-ion batteries, but their performance of fast charging and discharging and short-time high-power output is poor, so it is necessary to develop lithium-ion batteries with high-rate fast charging. The diaphragm is one of the important components of lithium-ion batteries. It not only isolates the positive and negative electrodes in the battery and prevents the positive and negative electrodes from directly contacting and short-circuiting, but also provides diffusion channels for the migration of lithium ions through its tortuous channels. Therefore, the performance of the diaphragm affects the diffusion rate of lithium ions, the retention of the electrolyte, the internal resistance of the system and the battery interface.

[0003] The diaphragms used in existing lithium batteries have poor electrolyte retention and a small compression ratio, which makes lithium batteries prone to lithium deposition during high-rate charging. The main reason is that the electrolyte is consumed too quickly during fast charging. At the same time, the expansion of the battery cell causes the gap between the pole pieces to decrease, and the electrolyte is insufficiently replenished, resulting in insufficient electrolyte content in the later stage and lithium deposition. The area with the greatest cell expansion stress is the corner area of ​​the cell, which results in the most significant electrolyte consumption in the corner area of ​​the cell during the cycle, and the risk of lithium deposition is particularly prominent. Therefore, there is an urgent need to develop a diaphragm with excellent electrolyte retention performance and a coating with a large compression ratio. Summary of the invention

[0004] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a wound battery and its application. The wound battery of the present invention can increase the interlayer spacing in the corner area of ​​the electrochemical device, improve the electrolyte retention capacity in the corner area, improve the problem of lithium precipitation in the corner during long cycles, reduce the thickness of the battery cell and improve the flatness of the battery cell, improve the energy density, and can be widely used in electrochemical devices.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect of the present invention, there is provided a wound battery, comprising a stacked and wound positive electrode sheet, a separator and a negative electrode sheet, wherein the wound battery comprises a straight region and corner regions connected to both ends of the straight region;

[0008] In the corner area, the maximum spacing between the adjacent positive electrode sheets and the negative electrode sheets is A μm; in the straight area, the maximum spacing between the adjacent positive electrode sheets and the negative electrode sheets is B μm, where 3≤AB≤10;

[0009] The diaphragm comprises a substrate and a polymer coating arranged on at least one side surface of the substrate, the compression ratio of the polymer coating is C, 40%≤C≤70%; the polymer coating comprises polymer particles with a particle size Dv50 of 2 to 20 μm.

[0010] The present invention proposes that the spacing Aμm between electrode layers in the corner area and the spacing Bμm between electrode layers in the straight area of ​​the wound battery must satisfy 3≤AB≤10. The spacing between electrode layers in the corner area of ​​the wound battery is increased, and the infiltration rate and liquid retention amount of the electrolyte in the corner area are improved, thereby improving the problem of electrolyte deficiency and lithium precipitation in the corners of the battery cell during long-cycle.

[0011] On the contrary, when AB is less than 3, the interlayer spacing in the corner area is too small, the electrolyte retention in the corner area is insufficient, and the improvement effect of lithium deposition in the corner is not good; when AB is greater than 10, the reserved interlayer spacing in the corner area is too large, the ion transmission path is too long, and poor lithium insertion and lithium deposition occur during the cycle, which has a negative impact on the corner area.

[0012] In order to realize the wound battery structure, the present invention also proposes that the diaphragm includes a substrate and a polymer coating arranged on at least one side of the surface, wherein the polymer coating is compressible, and the compression ratio C of the polymer coating is 40%≤C≤70%. This condition can ensure that the corner spacing of the wound battery is within the required range. On the one hand, the greater the compression of the polymer coating in the flat area, the smaller the proportion of the polymer coating thickness, and the thinner the wound battery; on the other hand, the greater the compression of the polymer coating in the straight area, the higher the flatness of the coating after compression, and the higher the flatness of the wound battery.

[0013] On the contrary, when C>70%, the polymer coating is compressed too much, the gaps between the polymer particles are closed, and the gaps in the base film are blocked, which may lead to the risk of lithium precipitation.

[0014] In addition, the polymer coating includes polymer particles with a particle size Dv50 of 2 to 20 μm. This specific particle size is conducive to regulating the compression ratio C of the polymer coating and cooperates with C to ensure the interlayer spacing.

[0015] In some embodiments of the present invention, the corner region is layered along the Z direction, ie, the thickness direction.

[0016] In some embodiments of the present invention, the straight region is layered along the Z direction, ie, the thickness direction.

[0017] In some embodiments of the present invention, 3≤AB≤10, for example, 3≤AB≤6, 3≤AB≤5, 3≤AB≤4, 3≤AB≤3.5, 3.5≤AB≤4, 3.5≤AB≤4.5, 4≤AB≤4.5, 8≤AB≤10, 8≤AB≤9, 9≤AB≤10.

[0018] In some embodiments of the present invention, in the corner area, the maximum spacing between adjacent positive electrode sheets and negative electrode sheets is 4-30 μm, for example, 6-30 μm, 8-30 μm, 10-30 μm, 12-30 μm, 12-25 μm, 12-15 μm, 15-30 μm, 15-25 μm, 25-30 μm.

[0019] In some embodiments of the present invention, in the straight area, the maximum spacing between adjacent positive electrode sheets and negative electrode sheets is 5.2-35 μm, for example, 5.2-30 μm, 6-30 μm, 6-25 μm, 9-25 μm, 9-24 μm, 9-21 μm, 10-20 μm.

[0020] In some embodiments of the present invention, the thickness of the polymer coating is H μm, wherein 3≤H×C≤10, to solve the lithium plating problem.

[0021] In some embodiments of the present invention, 3≤H×C≤10, for example, 3≤H×C≤6, 3≤H×C≤5, 3≤H×C≤4, 3≤H×C≤3.5, 3.5≤H×C≤4, 3.5≤H×C≤4.5, 4≤H×C≤4.5, 8≤H×C≤10, 8≤H×C≤9, and 9≤H×C≤10.

[0022] In some embodiments of the present invention, the particle size Dv50 of the polymer particles is 2 to 20 μm, for example, 2 to 18 μm, 2 to 15 μm, 2 to 12 μm, 2 to 10 μm, 2 to 9 μm, 3 to 15 μm, 3 to 12 μm, 3 to 10 μm, 3 to 9 μm, 4 to 12 μm, 4 to 10 μm, 6 to 12 μm. Preferably, the particle size Dv50 of the polymer particles is 4 to 12 μm. In the present invention, the volume average particle size Dv50 refers to the particle size corresponding to the cumulative volume distribution percentage reaching 50%, which is measured by using a laser particle size analyzer (e.g., Malvern Master Size 3000).

[0023] In some embodiments of the present invention, the polymer particles are selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyacrylonitrile, polymethyl methacrylate, cellulose acetate, butyl cellulose acetate, propyl cellulose acetate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, and acrylonitrile styrene butadiene copolymer. After compression, the polymer particles of the specific particle size of the present invention can still retain ion channels and do not deteriorate the cycle performance.

[0024] In some embodiments of the present invention, the polymer coating further comprises at least one of a binder, a thickener, and a wetting agent;

[0025] Wherein, the binder is selected from at least one of methacrylate binders, acrylic binders, and acrylate binders; and / or, the thickener is selected from at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or, the wetting agent is selected from at least one of dimethylsiloxane, polyethylene oxide, oxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer, and dioctyl sodium sulfosuccinate.

[0026] In some embodiments of the present invention, the raw materials for preparing the polymer coating include polymer particles, a binder, a thickener and a wetting agent, wherein, based on the total mass of the polymer coating, the mass proportion of the polymer particles is 85% to 95%, for example, 88% to 92%, 90%; based on the total mass of the polymer coating, the mass proportion of the binder is 3% to 9%, for example, 4% to 8%, 6%; based on the total mass of the polymer coating, the mass proportion of the thickener is 0.5% to 2%, for example, 1%; based on the total mass of the polymer coating, the mass proportion of the wetting agent is 0.5% to 5%, for example, 0.5% to 4%, 3%.

[0027] In some embodiments of the present invention, the polymer coating has a thickness of 4 to 30 μm, for example, 4 to 25 μm, 4 to 20 μm, 6 to 25 μm, 6 to 20 μm, 4 to 10 μm, 10 to 30 μm, or 15 to 25 μm.

[0028] In some embodiments of the present invention, the surface density of the polymer coating is 0.1 to 0.5 g / m 2 , for example, 0.2 to 0.5 g / m 2 , 0.3~0.5g / m 2 .

[0029] In some embodiments of the present invention, the substrate includes a porous base membrane and a ceramic coating disposed on at least one side of the porous base membrane. Coating the ceramic layer on the porous base membrane is beneficial to improving the thermal shrinkage of the diaphragm.

[0030] In some embodiments of the present invention, the porous base membrane has a thickness of 2 to 20 μm.

[0031] In some embodiments of the present invention, the thickness of the ceramic coating is 0.2-5 μm.

[0032] In some embodiments of the present invention, the material of the porous base film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyparaphenylene, polynaphthalene, polyimide, polyamide, aramid, and polyparaphenylene benzodithiazole.

[0033] In some embodiments of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer is disposed on at least one side of the negative electrode current collector.

[0034] In some embodiments of the present invention, the negative electrode current collector may be selected from a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0035] In some embodiments of the present invention, the negative electrode active material layer may use negative electrode active materials for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and titanates. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, or silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, or tin alloys. When the battery is a lithium-ion battery, lithium titanate is used as the titanate; when the battery is a sodium-ion battery, sodium titanate is used as the titanate. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0036] In some embodiments of the present invention, the negative electrode active material layer optionally includes a binder, which is selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), or carboxymethyl chitosan (CMCS).

[0037] In some embodiments of the present invention, based on the total mass of the negative electrode active material layer, the mass proportion of the binder is 0.5% to 3%.

[0038] In some embodiments of the present invention, the negative electrode active material layer optionally includes a conductive agent, which is selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0039] In some embodiments of the present invention, based on the total mass of the negative electrode active material layer, the mass proportion of the conductive agent is 0.8% to 4%.

[0040] In some embodiments of the present invention, the negative electrode active material layer optionally includes other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).

[0041] In some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, optionally including a binder, optionally including a conductive agent, and optionally other additives are dispersed in a solvent (such as deionized water) in proportion to form a negative electrode slurry; then the first negative electrode slurry is coated on both sides or one side of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode slurry is obtained.

[0042] In some embodiments of the present invention, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is disposed on at least one side of the positive electrode current collector.

[0043] In some embodiments of the present invention, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) on a substrate.

[0044] In some embodiments of the present invention, the positive electrode active material layer may use a positive electrode active material for a battery known in the art. As an example, when the positive electrode plate is used for a lithium-ion battery, the positive electrode active material may use a positive electrode active material for a lithium-ion battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as NCM333, NCM523, NCM211, NCM622, NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate or a composite material of lithium iron manganese phosphate and carbon. As an example, when the positive electrode plate is used in a sodium ion battery, the positive electrode active material may adopt a positive electrode active material for sodium ion batteries known in the art. As an example, the positive electrode active material may include, but is not limited to, at least one of a layered transition metal oxide, a polyanion compound, and a Prussian blue analog.

[0045] In some embodiments of the present invention, the positive electrode active material layer optionally includes a binder. The binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0046] In some embodiments of the present invention, based on the total mass of the positive electrode active material layer, the mass proportion of the binder is 0.5% to 3%.

[0047] In some embodiments of the present invention, the positive electrode active material layer optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0048] In some embodiments of the present invention, based on the total mass of the positive electrode active material layer, the mass proportion of the conductive agent is 0.8% to 4%.

[0049] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the optional conductive agent, the optional binder and the optional other auxiliary agents are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode slurry is obtained.

[0050] The present invention has no specific limitation on the type of electrolyte, which can be selected according to the requirements. For example, the electrolyte can be a liquid electrolyte, a gel electrolyte or a fully solid electrolyte.

[0051] In some embodiments of the present invention, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0052] In some embodiments of the present invention, when the battery is a lithium ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, or lithium tetrafluorooxalate phosphate. When the battery is a sodium ion battery, the electrolyte salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium tetrafluoroborate, sodium bis(oxalate borate), sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethanesulfonate, or sodium bis(trifluoromethanesulfonyl)imide.

[0053] In some embodiments of the present invention, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0054] In some embodiments of the present invention, the electrolyte may further include additives. The additives include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0055] A second aspect of the present invention provides a method for preparing the above-mentioned wound battery, comprising the following steps:

[0056] The positive electrode sheet, the negative electrode sheet and the separator are stacked in sequence and prepared by winding.

[0057] According to a third aspect of the present invention, there is provided an electrical device, wherein the electrical device comprises the above-mentioned wound battery.

[0058] The wound battery of the present invention can be used in electrical devices that use batteries as power sources or various energy storage systems that use batteries as energy storage elements. Electrical devices may include but are not limited to mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc.

[0059] According to some preferred embodiments of the present invention, at least the following beneficial effects are achieved:

[0060] The present invention designs a compressible diaphragm coating to increase the distance between the pole pieces in the corner area of ​​the electrochemical device containing the polymer diaphragm coating, improve the electrolyte infiltration rate and liquid retention in the corner area, and improve the problem of lithium precipitation in the corner of the battery cell during long-cycle electrolyte shortage. The present invention does not involve equipment modification, does not have a negative impact on the chemical system, has a simple solution, low cost, no performance loss, and high promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0062] Figure 1 It is a schematic diagram of the cross-sectional structure of the battery cell in the thickness direction;

[0063] Figure 2 It is a schematic diagram of the cross-sectional structure of the diaphragm in the thickness direction;

[0064] Among them, the reference numerals in the figures are:

[0065] 100, straight area, 200, corner area, 300, maximum distance between adjacent positive and negative pole pieces in the corner area of ​​the battery cell, 400, maximum distance between adjacent positive and negative pole pieces in the straight area of ​​the battery cell;

[0066] 1. Porous substrate, 2. Ceramic coating, 3. Polymer coating. DETAILED DESCRIPTION

[0067] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0068] Example

[0069] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0070] In addition, in order to facilitate the description of the scheme and effect of the present invention, the following embodiments are all based on Figure 1 and Figure 2 The structure shown is used as an example. The wound battery of the present invention comprises a stacked and wound positive electrode sheet, a separator and a negative electrode sheet, and the wound battery comprises a straight region 100 and a corner region 200 connected to both ends of the straight region; wherein, in the corner region 200, there is a maximum interlayer spacing of 300 between adjacent positive electrode sheets and negative electrode sheets; and in the straight region 100, there is a maximum interlayer spacing of 400 between adjacent positive electrode sheets and negative electrode sheets. The separator comprises a substrate and a polymer coating 3 disposed on at least one side surface of the substrate, wherein the substrate comprises a porous substrate 1 and a ceramic coating 2 disposed on at least one side surface of the porous substrate 1.

[0071] Hereinafter, embodiments of the present invention will be described in more detail with reference to Examples 1 to 12.

[0072] Example 1

[0073] This embodiment provides a wound battery and a method for preparing the same.

[0074] Preparation of positive electrode sheet: The positive electrode active material LiCoO2, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one side of a positive electrode current collector aluminum foil with a thickness of 10μm, and the aluminum foil is dried at 120℃ for 1h to obtain a positive electrode coated with a positive electrode material layer on one side. Repeat the above steps on the other side of the aluminum foil to obtain a positive electrode coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120℃ for 1h to obtain a positive electrode sheet with a specification of 70mm×865mm.

[0075] Preparation of negative electrode sheet: Mix the negative electrode active material graphite, binder styrene butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 98:1:1, add deionized water, and stir evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 50wt%. The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil with a thickness of 8μm, and the copper foil is dried at 120°C to obtain a negative electrode coated with a negative electrode material layer on one side. Repeat the above steps on the other side of the aluminum foil to obtain a negative electrode coated with a negative electrode material layer on both sides. Then, after cold pressing, cutting and slitting, it is dried under vacuum conditions at 120°C for 1h to obtain a negative electrode sheet with a specification of 74mm×873mm.

[0076] Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), propylene carbonate (PC) and dimethyl carbonate (DMC) were mixed in a mass ratio of 3:2:4 to obtain an organic solvent, and then lithium salt lithium hexafluorophosphate was added to the organic solvent at a concentration of 1 mol / L to obtain an electrolyte.

[0077] Preparation of the diaphragm: Mix polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 5 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) in a mass ratio of 90:6:1:3, add water and stir evenly to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is evenly coated on the surface of a porous polyethylene substrate containing a ceramic coating by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6 μm, the compression ratio of the polymer coating is 30%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0078] Preparation of lithium-ion battery: stack the positive electrode, separator and negative electrode prepared above in order, place the separator between the positive electrode and the negative electrode to play a role of isolation, and wind to obtain an electrode assembly. Place the electrode assembly in an aluminum-plastic film packaging bag, inject electrolyte after drying, and obtain a lithium-ion battery through vacuum packaging, standing, formation, degassing, trimming and other processes.

[0079] Example 2

[0080] Example 2 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 2 and Example 1 is that the compression ratio of the polymer coating of the separator is 40%.

[0081] Specifically, a polymer coating with a compression ratio of 40% is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 5.5 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6 μm, the compression ratio of the polymer coating is 40%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0082] Example 3

[0083] Example 3 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 3 and Example 1 is that the compression ratio of the polymer coating of the separator is 50%.

[0084] Specifically, a polymer coating with a compression ratio of 50% is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 6 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6 μm, the compression ratio of the polymer coating is 50%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0085] Example 4

[0086] Example 4 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 4 and Example 1 is that the compression ratio of the polymer coating of the separator is 60%.

[0087] Specifically, a polymer coating with a compression ratio of 60% is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 6 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6 μm, the compression ratio of the polymer coating is 60%, and the surface density of the polymer coating is 0.45 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0088] Example 5

[0089] Example 5 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 5 and Example 1 is that the compression ratio of the polymer coating of the separator is 70%.

[0090] Specifically, a polymer coating with a compression ratio of 70% is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 6 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6 μm, the compression ratio of the polymer coating is 70%, and the surface density of the polymer coating is 0.4 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0091] Example 6

[0092] Example 6 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 6 and Example 1 is that the compression ratio of the polymer coating of the separator is 80%.

[0093] Specifically, a polymer coating with a compression ratio of 80% is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 6 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6 μm, the compression ratio of the polymer coating is 80%, and the surface density of the polymer coating is 0.35 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0094] Example 7

[0095] Example 7 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 7 and Example 1 is that the compression ratio of the polymer coating of the separator is 90%.

[0096] Specifically, a polymer coating with a compression ratio of 90% is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 5 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 6μm, the compression ratio of the polymer coating is 90%, and the surface density of the polymer coating is 0.3g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0097] Example 8

[0098] Example 8 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 8 and Example 1 is that the compression ratio of the polymer coating of the diaphragm is 40% and the coating thickness is 20 μm.

[0099] Specifically, a polymer coating with a compression ratio of 40% and a coating thickness of 20 μm is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 12 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 20 μm, the compression ratio of the polymer coating is 40%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0100] Example 9

[0101] Example 9 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 9 and Example 1 is that the compression ratio of the polymer coating of the diaphragm is 50% and the coating thickness is 20 μm.

[0102] Specifically, a polymer coating with a compression ratio of 50% and a coating thickness of 20 μm is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 10 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 20 μm, the compression ratio of the polymer coating is 50%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0103] Example 10

[0104] Example 10 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 1 and Example 1 is that the compression ratio of the polymer coating of the separator is 60% and the coating thickness is 20 μm.

[0105] Specifically, a polymer coating with a compression ratio of 60% and a coating thickness of 20 μm is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 8 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 20 μm, the compression ratio of the polymer coating is 60%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0106] Embodiment 11

[0107] Example 11 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between Example 1 and Example 1 is that the compression ratio of the polymer coating of the diaphragm is 70% and the coating thickness is 20 μm.

[0108] Specifically, a polymer coating with a compression ratio of 70% and a coating thickness of 20 μm is obtained by the following means: polyvinylidene fluoride-hexafluoropropylene copolymer with a secondary particle size Dv50 of 6 μm, isobutyl acrylate polymer (binder), sodium carboxymethyl cellulose (thickener) and polyoxyethylene fatty alcohol ether (wetting agent) are mixed in a mass ratio of 90:6:1:3, and stirred evenly after adding water to obtain a polymer coating slurry with a solid content of 12 wt%. The polymer coating slurry is uniformly coated on the surface of a porous polyethylene substrate containing a ceramic coating on the surface by a micro-concave roller coating method, and then dried at 60°C to obtain a diaphragm coated with a polymer coating on one side. Among them, the thickness of the polymer coating is 20 μm, the compression ratio of the polymer coating is 70%, and the surface density of the polymer coating is 0.5 g / m 2 , the thickness of the porous polyethylene substrate is 7 μm, and the thickness of the ceramic coating is 2 μm.

[0109] Example 12

[0110] Example 12 provides a wound battery and a preparation method thereof, which is specifically carried out with reference to Example 1. The difference between it and Example 1 is that the thickness of the polymer coating of the diaphragm is 1 μm, the compression ratio is 0, and the secondary particle size Dv50 of the polyvinylidene fluoride-hexafluoropropylene copolymer is 1 μm.

[0111] The following parameters of the cells prepared in Examples 1 to 12 were measured:

[0112] (1) In the corner area of ​​the battery cell, the maximum spacing between adjacent positive and negative electrode sheets is Aμm;

[0113] (2) In the straight area of ​​the battery cell, the maximum spacing between adjacent positive and negative electrode sheets is B μm;

[0114] The measurement method used is: using computed tomography (CT) technology to measure the corner layer spacing and main body layer spacing of the battery cross section, repeating the measurement 5 times and taking the average value;

[0115] (3) Compression ratio of polymer coating;

[0116] The measurement method used is: after formation, a separator sample is obtained from the flat area of ​​the battery cell, and the thickness M of the polymer coating after formation and the thickness N of the polymer coating before winding are measured by cross-section polishing-scanning electron microscopy (CP-SEM), and the measurements are repeated 5 times to take the average value. The compression ratio of the polymer coating is calculated as C = (NM) / N×100%.

[0117] The measurement results of the above factors are shown in Table 1.

[0118] Table 1

[0119]

[0120]

[0121] Performance Testing

[0122] Record the thickness and flatness of the battery cell, test the capacity retention rate of the battery cell at room temperature 4C cycle @1000 cycles, and the lithium deposition in the anode material area. The test method is as follows:

[0123] (1) Cell flatness test: The 3D profilometer tests the cell thickness distribution. Cell flatness = maximum cell thickness - minimum cell thickness.

[0124] (2) Battery cell room temperature 4C cycle system: Place the lithium-ion battery in a 25℃ environment, let it stand for 30 minutes, charge it at 4C constant current to 4.50V, then charge it at 4.50V constant voltage to 0.05C, let it stand for 5 minutes, and discharge it at 1C constant current to 3.0V. The cycle charge and discharge is 800 times.

[0125] (3) Determination of lithium deposition level in the straight area of ​​the anode (observation with naked eyes, taking photos to measure the size of the lithium deposition area):

[0126] No lithium deposition: no lithium deposition on the surface of the main area of ​​the anode sheet;

[0127] Slight lithium deposition: The lithium deposition area on the surface of the main area of ​​the anode sheet is less than 5%;

[0128] Moderate lithium deposition: The lithium deposition area on the surface of the main area of ​​the anode sheet is 5% to 20%;

[0129] Severe lithium deposition: The lithium deposition area on the surface of the main area of ​​the anode sheet is greater than 20%.

[0130] (4) Determination of lithium deposition level in the anode corner area (observation with naked eyes, taking photos to measure the size of the lithium deposition area):

[0131] No lithium deposition: no lithium deposition on the surface of the corner area of ​​the anode sheet;

[0132] Slight lithium deposition: The lithium deposition area on the corner of the anode is less than 10% and does not grow to the straight area;

[0133] Moderate lithium deposition: The lithium deposition area on the anode surface is 10% to 40%, and does not grow to a flat area;

[0134] Severe lithium deposition: The lithium deposition area on the surface of the anode sheet is greater than 40%, or grows to a flat area.

[0135] The performance test results are shown in Table 2 below.

[0136] Table 2

[0137]

[0138]

[0139] It can be seen from Examples 1, 2, and 12 that when AB<3, the interlayer spacing in the corner area is too small, and there is a problem of lithium deposition in the corners during the cycle.

[0140] It can be seen from Examples 10 and 11 that when AB>10, the interlayer spacing in the corner area is too large, the ion transmission path is too long, poor lithium insertion and lithium deposition occur during the cycle, and there is a problem of lithium deposition at the corners during the cycle.

[0141] It can be seen from Examples 3 to 9 that when 3≤AB≤10, the problem of lithium deposition at the corners of the battery cell during long cycles due to lack of liquid is improved, and the problem of lithium deposition at the corners of the cycle is significantly improved.

[0142] From the comparison of Examples 1-7, it can be seen that the compression ratio C of the polymer coating satisfies 40%≤C≤70%. When the thickness H of the polymer coating is the same, the smaller the initial thickness of the battery cell, the higher the flatness. When C>70%, the polymer coating is compressed too much, the gaps between the polymer particles are closed, the gaps in the base film are blocked, and there is a risk of lithium plating.

[0143] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A wound battery, characterized in that: The wound battery comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound, wherein the wound battery comprises a straight area and corner areas connected to both ends of the straight area; In the corner area, the maximum spacing between the adjacent positive electrode sheets and the negative electrode sheets is A μm; in the straight area, the maximum spacing between the adjacent positive electrode sheets and the negative electrode sheets is B μm, where 3≤AB≤10; The diaphragm comprises a substrate and a polymer coating arranged on at least one side surface of the substrate, the compression ratio of the polymer coating is C, 40%≤C≤70%; the polymer coating comprises polymer particles with a particle size Dv50 of 2 to 20 μm.

2. The wound battery according to claim 1, characterized in that: The thickness of the polymer coating is H μm, wherein 3≤H×C≤10.

3. The wound battery according to claim 1, characterized in that: The B=5.2~35.

4. The wound battery according to claim 1, characterized in that: The particle size Dv50 of the polymer particles is 4 to 12 μm.

5. The wound battery according to claim 1, characterized in that: The polymer particles are selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyacrylonitrile, polymethyl methacrylate, cellulose acetate, butyl cellulose acetate, propyl cellulose acetate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, and acrylonitrile styrene butadiene copolymer.

6. The wound battery according to claim 1, characterized in that: The polymer coating further comprises at least one of a binder, a thickener, and a wetting agent; Wherein, the binder is selected from at least one of methacrylate binders, acrylic binders, and acrylate binders; and / or, the thickener is selected from at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or, the wetting agent is selected from at least one of dimethylsiloxane, polyethylene oxide, oxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer, and dioctyl sodium sulfosuccinate.

7. The wound battery according to claim 1, characterized in that: The surface density of the polymer coating is 0.1 to 0.5 g / m 2 .

8. The wound battery according to claim 1, characterized in that: The substrate includes a porous base membrane and a ceramic coating disposed on at least one side surface of the porous base membrane.

9. The wound battery according to claim 8, characterized in that: The thickness of the porous base film is 2 to 20 μm; and / or, The thickness of the ceramic coating is 0.2 to 5 μm; and / or, The material of the porous base film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyparaphenylene, polynaphthalene, polyimide, polyamide, aramid, and polyparaphenylene benzodithiazole.

10. An electrical device, characterized in that: A wound battery comprising the battery according to any one of claims 1 to 9.

Citation Information

Cited By

  • Battery monomer, preparation method thereof, battery device and power utilization device

    CN120810191A

  • Battery and electric device

    WO2026184696A1